Categorial shift: foundations, extensions, and consequences. (May 2019) - Mithun, Marianne
Abstract: As the papers in this volume make clear, categorial shift is often not categorical . Category-altering processes do not necessarily shift all morphological, syntactic, and semantic properties of their input simultaneously or completely (Noonan, 1985/2007; Mackenzie, 1987; Lehmann, 1988; Givón 1990, 2001, 2011; Croft, 1991; Koptjevskaja-Tamm, 1993, 2003; Cristofaro, 2003; Malchukov, 2004, 2006; Nikolaeva, 2007; Mithun, 2016a ). A number of factors can affect the output of such processes, their course of development, and their consequences for the shapes of grammars. Here each of these issues is examined in turn. First is the identification of the lexical categories involved in the shifts: the structural level at which they take place (roots, bases, stems, words) and the criteria by which they are defined (morphological, syntactic, semantic). Also pertinent here is the nature of the shift processes, in particular, conversion. Second are some recurring trajectories of development of shift processes involving their extension to larger domains of structure. Third are some effects categorial shift processes can have on other aspects of grammar. Highlights: Shifting categories may be roots, bases, stems, words, or phrases. Criteria for categorization may be morphological and/or syntactic. Conversion (or zero derivation) may take place at any level. Shifts may be extended over time from lower to higher levels of structure. Shifts may trigger other grammatical developments, i.e. new categories and paradigms.